Adherence to the “Atrial fibrillation Better Care” (ABC) pathway in patients with atrial fibrillation and cancer: A report from the ESC-EHRA EURObservational Research Programme in atrial fibrillation (EORP-AF) General Long-Term Registry - Vitolo, Marco; Proietti, Marco; Malavasi, Vincenzo L.; Bonini, Niccolo’; Romiti, Giulio Francesco; Imberti, Jacopo F.; Fauchier, Laurent; Marin, Francisco; Nabauer, Michael; Potpara, Tatjana S.; Dan, Gheorghe-Andrei; Kalarus, Zbigniew; et al. (European journal of internal medicine, 2022)
•Appropriate management of AF patients with cancer in real-world clinical practice is challenging.•In this EORP-AF study, we analyzed a cohort of AF patients with prior or active cancer.•A structured approach based on the “Atrial fibrillation Better Care” (ABC) Pathway is still suboptimal.•Adherence to the “C” criterion (i.e. management of comorbidities) was more critical, being specifically lower in cancer patients.•Adherence to the ABC pathway was independently associated with a lower risk outcomes. Implementation of the Atrial fibrillation Better Care (ABC) pathway is recommended by guidelines on atrial fibrillation (AF), but the impact of adherence to ABC pathway in patients with cancer is unknown. To investigate the adherence to ABC pathway and its impact on adverse outcomes in AF patients with cancer. Patients enrolled in the EORP-AF General Long-Term Registry were analyzed according to (i) No Cancer; and (ii) Prior or active cancer and stratified in relation to adherence to the ABC pathway. The composite Net Clinical Outcome (NCO) of all-cause death, major adverse cardiovascular events and major bleeding was the primary endpoint. Among 6550 patients (median age 69 years, females 40.1%), 6005 (91.7%) had no cancer, while 545 (8.3%) had a diagnosis of active or prior cancer at baseline, with the proportions of full adherence to ABC pathway of 30.6% and 25.7%, respectively. Adherence to the ABC pathway was associated with a significantly lower occurrence of the primary outcome vs. non-adherence, both in ‘no cancer’ and ‘cancer’ patients [adjusted Hazard Ratio (aHR) 0.78, 95% confidence interval (CI): 0.66–0.92 and aHR 0.59, 95% CI 0.37–0.96, respectively]. Adherence to a higher number of ABC criteria was associated with a lower risk of the primary outcome, being lowest when 3 ABC criteria were fulfilled (no cancer: aHR 0.54, 95%CI: 0.36–0.81; with cancer: aHR 0.32, 95% CI 0.13–0.78). In AF patients with cancer enrolled in the EORP-AF General Long-Term Registry, adherence to ABC pathway was sub-optimal. Full adherence to ABC-pathway was associated with a lower risk of adverse events [Display omitted] Adherence to the “Atrial fibrillation Better Care” (ABC) pathway in patients with atrial fibrillation and cancer and its impact on clinical outcomes.